Glazed Bowl with Persian Pottery from Azak - Iudin Nikita I.; Maslovsky Andrey N.; Kazempur Mehdi (Поволжская археология, 2022)
The article presents translation of the inscriptions on a big glazed bowl of Azerbaijani origin from the excavations of Azak. This find is unique for the archaeology of the Golden Horde. For the first time, since the moment of discovery, full translation, the preserved part of an inscription is published. The poetic text belongs to the previously unknown poet, Mokhi Al Din Ali Olnasser. This is one of the most voluminous epigraphic monuments found during the excavations of the Golden Horde sites. A fragment from the Samosdelka settlement, which bears the name of the master potter, Mahmud ibn Yusuf, probably comes from a bowl with a similar inscription. The work also provides information about the share and chronology of Shirvan ceramics in the complex of finds from Azak and other cities of the Golden Horde, gives its technological description and cites some of the most striking images.